SISTEM INFORMASI PENGAWASAN PINJAMAN DAERAH OLEH KEMENTERIAN DALAM NEGERI - Jhon Roy H. Siagian; Ionia Veritawati (JURNAL ILMIAH INFORMATIKA, 2020)
The 4.0 industrial revolution demands that government services be connected online. The Ministry of Home Affairs can provide services to Local Governments by utilizing technology related to giving the Minister of Home Affairs considerations on regional loans to be easier, faster and electronically documented. At present all Local Governments deliver physical documents directly to the Ministry of the Interior's office to propose consideration regarding regional loans. This is felt to be less effective, due to the high cost of delivering physical documents through official travel, storing data on one computer that is not transparent, and physical documents not documented electronically. This jurnal has developed a regional loan supervision information system using a codeigniter framework using the waterfall method, and using UML and data collection techniques using observation, interviews and literature study methods. The procedures examined include the submission of a request by the regional government along with the required documents, verification and confirmation, filling out the worksheet, submitting the results of consideration, and submitting the report of the Regional Government. The results of this study are expected to provide convenience, the principle of transparency and can do documentation electronically.